Use of Osteofasciocutaneous Fibular Free Flap and Radial Head Arthroplasty in Trauma for Limb Salvage and Continued Elbow Function - Catherine Kilmartin; Katharine D. Harper; Chirag Mehta; Joseph Thoder; Andrew Newman (Case Reports in Orthopedics)
Reconstructive flaps have revolutionized the ability of surgeons to restore function and cosmesis for patients. While reconstructive flaps have been used to bridge large defects due to oncologic or congenital maladies necessitating large debridements, few cases have observed salvage flaps in traumas which provide additional challenges secondary to an injury trajectory. This case report details use of an osteofasciocutaneous fibular free flap and radial head prosthesis to restore forearm function in a 64-year-old female with a comminuted fracture of the proximal radius. The patient has sustained a 5.5 cm epiphyseal radial defect with an associated 20 × 15 cm overlying tissue defect after serial debridement. In review of the literature, only one nontraumatic case using a combined free flap and radial head prosthesis for proximal forearm defect to restore joint function has been reported. We suggest that, for proximal forearm fractures, this technique can be used to restore elbow joint function in limb salvage.